2020
DOI: 10.1016/j.jamcollsurg.2020.08.068
|View full text |Cite
|
Sign up to set email alerts
|

Predictors for Persistent Perioperative Symptoms after a Cesarean Section at a Hospital in Rural Rwanda

Abstract: elective operations pre and post-program (mean:38.4AE7.9/month vs 38.3AE9.0/month; p ¼ 0.944). Postoperative complication included wound infection (n ¼ 3;6.1%), pain (n ¼ 2;4.1%) and hematoma/ seroma (n ¼ 4;8.2%). There were no recurrences, and 98.0% (n ¼ 48) of participants were satisfied. CONCLUSION: Implementation of the task-sharing training program was associated with an increase in the number of mesh and total elective IHRs. However, there was no change in the rate of total elective surgical procedures. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This association could be explained in the context of poor health outcomes previously reported among poor postpartum women. Poverty has been associated with poor postpartum nutritional status [ 49 , 50 ], incidence of SSI [ 22 , 51 ] and poor post-natal care [ 52 ]. A study in Ethiopia reported that irrespective of mode of delivery, women with low income were almost half as likely to seek postpartum care [ 53 ], and a study in Iran found that rural women who did not receive enhanced postpartum follow-up reported poor functional status at six weeks postpartum [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…This association could be explained in the context of poor health outcomes previously reported among poor postpartum women. Poverty has been associated with poor postpartum nutritional status [ 49 , 50 ], incidence of SSI [ 22 , 51 ] and poor post-natal care [ 52 ]. A study in Ethiopia reported that irrespective of mode of delivery, women with low income were almost half as likely to seek postpartum care [ 53 ], and a study in Iran found that rural women who did not receive enhanced postpartum follow-up reported poor functional status at six weeks postpartum [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…This association could be explained in the context of poor health outcomes previously reported among poor postpartum women. Poverty has been associated with poor postpartum nutritional status [37,38], incidence of SSIs [17,39], and poor post-natal care [40]. A study in Ethiopia reported that irrespective of mode of delivery, women with low income were almost half as likely to seek postpartum care [41], and a study in Iran found that rural women who did not received enhanced postpartum follow-up reported poor functional status at six weeks postpartum [41].…”
Section: Discussionmentioning
confidence: 99%